Collaborative Writing on Descriptive Text: Creativity and Engagement - Elga Farah Andanty; Agus Sholeh; Siti Mafulah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study aims to investigate the implementation of collaborative writing methods in improving creativity and engagement in writing descriptive texts at SMP Negeri 5 Kepanjen. This study uses a qualitative approach with a descriptive research type. Research data were collected through observation, interview and documentation activities. The collected data were analyzed descriptively qualitatively using an interactive data analysis model. The data from the research were re-tested for validity using triangulation. The results of the study showed that the implementation of the collaborative writing method in descriptive text learning increased As evidenced by the results of observations and interviews on student responses showed that collaborative writing can improve their creativity and engagement. This study highlights the potential of Collaborative Writing as a means to improve student creativity and engagement in descriptive text learning in junior high schools.